Risk factors associated with the acute renal damage induced by contrast media in patients revascularized by means of transluminal percutaneous angioplasty - Alberto Hernández González; Caridad de Dios Soler Morejón; Teddy Osmin Tamargo Barbeito; Dagoberto Semanat Vaillant; Frank Pérez Peña (Centro Provincial de Información de Ciencias Médicas, 2018)
Introduction: patients in need of transluminal percutaneous angioplasty have a high probability of presenting renal damage induced by means of contrast.  Objective: to determine the risk factors associated with the acute renal damage induced by this means of contrast.   Methods: descriptive study of 57 patients with heart disease who required  transluminal percutaneous angioplasty in the Cardiology Center of "Hermanos Ameijeiras" Clinical Surgical Hospital of Havana City, from January to December, 2016. Two groups were conformed for that purpose (with nephropathy and without it). It was considered the existence of renal damage if the serum creatinine increased in 25 % or more at the 72 hours of having carried out the procedure. The Mehran scale modified was used to stratify the risk.   Results: there was renal damage in 49.1% of the patients. The associated factors were the previous angiography, the urgent percutaneous transluminal angioplasty and the volume of contrast used. According to the scale of Mehran there was a prevalence of the affected patients in the groups of low and moderate risk; however, taking into account the identified risk factors, these patients prevailed in the groups of high and very high risk.   Conclusions: the previous angiography, the urgent realization of transluminal percutaneous angioplasty and the volume of contrast used increase the risk of renal damage. It was determined that the modified Mehran scale was not useful to stratify the patients of low risk.